Shaer yang di-Pertuan: Tinjuan Historis Relasi Umara dan Ulama di Brunei Darussalam - bin Kamis, Izzah Naqibah; bin Haji Masri, Muhammed Sahrin (FIKRAH, 2020)
Umara and Ulama are two groups who are very influential and has very basic relationships on the State of Brunei Darussalam's growth. Basically, Ulama are known as someone who inherits Anbiya's character, they play a role as murshid in Malay society. This phenomenon has been explained by the importance of their names in some rare materials such as manuscripts, stones and artifacts, hikayat and so on. But The Ulama rarely present it as a poetic/syair approach. The work of "Shaer Yang Di-Pertuan" is one of the poems/syair ever written and can be considered as the most important part of Brunei Darussalam. This poems/syair was written by Pehin Royal Khatib Awang Abdul Razak bin Hasanuddin, a famous Ulama from Brunei, around the late 19th and early 20th centuries. This poems/syair was produced by Pehin Siraja Khatib Awang Abdul Razak bin Hasanuddin, a famous Brunei Ulama around the end of the 19th century and the beginning of the 20th century. There are many important events during the reign of Sultan Muhammad Jamalul Alam II (26th Sultan of Brunei) featured in this poems/syair. Based on it background, this study will explain some of the key components of the "Syaer Yang Di-Pertuan". In addition, there are some explanations of how the umara-ulama relationship works at the same time will highlight some of the ulama who involved directly. This is because they have a significant influence on the struggle that took place at that time, especially in spreading Islam in the NBD and its role in the development of nationalism and governance in Brunei Darussalam